Utilization of alkali-activated slag based composite in deepwater oil well cementing. (20th October 2018) - Jiapei, Du; Yuhuan, Bu; Xuechao, Cao; Zhonghou, Shen; Baojiang, Sun
Highlights: SCA enhances early term compressive strength of AAS based composites. The dosage of resin affects the reaction degree. SCA can generate a thin membrane on the surface of slag particles. Resin and SCA influence the microstructure of reaction products of slag. Abstract: The compressive strength and setting time of alkali-activated slag (AAS) based composites under deepwater condition of curing is investigated. Test results show that the AAS based composites obtain high early term strength and proper setting property for practical operations. Resin weakened the compressive strength decreasing phenomenon while the doping of coupling agent significantly enhanced the early term compressive strength of AAS based composites. The excessive resin could cover the surface of slag particles and affect both reaction rate and reaction degree of slags. The setting time of AAS based composites extended effectively after the addition of silane coupling agent. The silane coupling agent generated a thin membrane on the surface of slag particles and reduced the reaction rate of AAS. The X-ray diffraction, scanning electron microscopy and energy dispersive X-ray spectroscopy analysis show that resin and coupling agent cannot affect the chemical properties of alkali-activated slag, but they influence the microstructure of reaction products of slag. Low dosage of resin (5%) provided a well bond and uncracked structure of the matrix. When the AAS incorporated high dosage of resin, large aggregates formed. The connection between these aggregates and AAS is very weak. The coupling agent can act as a compatibilizing agent to enhance the connection among different phases.